SNHG14 facilitates cell proliferation in colorectal cancer through targeting KRAS via Hippo-YAP signaling: SNHG14 exacerbates colorectal cancer - Shen, Minmin; Su, Yue; Song, Shaobo; Liu, Daocheng; Liu, Zhaohui; Chen, Dong; Pan, Yuan; Zhang, Lei; Xu, Xiaoping (Cellular and Molecular Biology, 2023)
Accumulating evidence indicates the significant role of lncRNAs in multiple biological processes and cancer progression. However, most lncRNAs in CRC remain to be excavated. In this study, we investigated SNHG14 in CRC. SNHG14 which was generally under-expressed in normal colon specimens revealed by UCSC was uncovered as markedly highly expressed in CRC cell lines. Besides, SNHG14 was a contributor to CRC cell proliferation. Additionally, we demonstrated that SNHG14 facilitated CRC cell proliferation in a KRAS-dependent manner. Moreover, the mechanistic investigations indicated that SNHG14 interacted with YAP and therefore inactivated the Hippo pathway, so as to enhance YAP-targeted KRAS expression in CRC. Furthermore, SNHG14 was explained as transcriptionally activated by FOS, a previously identified common effector molecule of KRAS and YAP. All in all, our findings elucidated a feedback loop of SNHG14/YAP/KRAS/FOS in facilitating CRC tumorigenesis, which may help develop novel effective targets for CRC patients.